A Simple Gas-Kinetic Model for Dilute and Weakly Charged Plasma Micro-Jet Flows - Shiying Cai; Chunpei Cai (Fluids, 2021)
This paper presents a simple model for slightly charged gas expanding into a vacuum from a planar exit. The number density, bulk velocity, temperature, and potential at the exit are given. The electric field force is assumed weaker than the convection term and is neglected in the analysis. As such, the quasi-neutral condition is naturally adopted and the potential field is computed with the Boltzmann relation. At far field, the exit degenerates as a point source, and simplified analytical formulas for flow and electric fields are obtained. The results are generic and offer insights on many existing models in the literature. They can be used to quickly approximate the flowfield and potential distributions without numerical simulations. They can also be used to initialize a simulation. Based on these results, more advanced models may be further developed.